Contemporary Sculpture from a private collection. - Heartney, Eleanor (New York : Zwirner & Wirth New York, 2006)
Abakanowicz, Magdalena ; Almond, Darren ; Balka, Miroslaw ; Bickerton, Ashley ; Butterfield, Deborah ; Edmier, Keith ; Eliasson, Olafur ; Friedman, Tom ; Gober, Robert ; Hamilton, Ann ; Hatoum, Mona ; Hirschhorn, Thomas ; Horn, Rebecca ; Knowlton, Win ; LeDray, Charles ; Muñoz, Juan ; Murakami, Takashi ; Neto, Ernesto ; Pondick, Rona ; Rhoades, Jason ; Smith, Kiki ; Steinbach, Haim ; Whiteread, Rachel
Contemporay Sculpture from a private collectio, Zwirner & Wirth, New York, 2006-09-14. 2006-10-14
boek